PENERAPAN TERAPI HEALING PSIKOSOSIAL BERBASIS LITERASI MEMBACA PADA ANAK KORBAN BANJIR SUMATERA UTARA - Novria Grahmayanuri; Fadhilah Syam Nasution; Siti Khodijah; Devi widya Ningsih; Fadhli Ihsan Arbas Hasibuan (LPPM IAD Probolinggo, 2026)
Flood disasters occurring in various areas of North Sumatra cause not only physical damage but also psychosocial impacts, particularly on children as a vulnerable group. Children affected by floods are at risk of experiencing anxiety, fear, and difficulties in expressing emotions after the disaster. This community service activity aimed to implement a reading literacy–based healing therapy as an effort to support the psychosocial recovery of children affected by floods in North Sumatra. The method employed was training through guided reading activities facilitated by trained facilitators, combined with simple discussions, storytelling, and emotional expression through drawing. The results indicated an improvement in children’s participation, emotional openness, and social interaction, along with a decrease in observable signs of anxiety after the implementation of the reading-based healing therapy. These findings suggest that reading literacy functions not only as an educational activity but also as an effective, accessible, and sustainable healing therapy to support children’s psychosocial recovery in post-flood disaster contexts.